Growth And Production Of Grass Panicum maximum cv. Trichoglume Which Are Planted With Legume Alysicarpus vaginalis With Different Dosage Phosphate Fertilizer - P., Suharto; Gaga Partama, I. B.; Budiasa, I K. M. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019DO - 10.24843/ejpt.2019.v07.i03.p09, 2019)
This Research to get information about the growth and production of Panicum maximum cv. Trichoglume which was associated with a combination of Alysicarpus vaginalis legumes and different dosage of phosphate fertilizer. This research has been carried out at the Laboratory of Greenhouse Laboratory Research Station, Faculty of Animal Husbandry, Udayana University with Completely randomized design (CRD) one factor with 9 combination was used in this experiment. The number of combination of Alysicarpus vaginalis legumes, included 1, 2, 3 Alysicarpus vaginalis /pot and dosage of phosphate fertilizer is: without fertilizer; 50 kg/ha; and 100 kg/ha. Variables observed were: plant height, number of leaves, number of tillers, number of branches, leaf dry weight, stem dry weight, root dry weight, total forage dry weight, leaf dry weight ratio with stem dry weight, total forage dry weight ratio dried roots, and leaf area. The experiment results showed there was effect on growth of Panicum maximum cv. Trichoglume grass which was associated with a combination of 1 Alysicarpus vaginalis with 100 kg/ha dosage of phosphate fertilizeron variables: number of tillers, leaf dry weight, total forage dry weight, and leaf dry weight ration with steam dry weight. It was showed that between associated with a combination of legumes and dosage of phosphate fertilizer can affect growth and production of Panicum grass maximum cv. Trichoglume. It can be concluded that the best results were obtained in associated with a combinationof1 Alysicarpus vaginalis legumes with a phospate fertilizer dosege of 100 kg/ha.   Keywords: growth and production, Panicum maximum cv. Trichoglume, phosphate fertilizer .